2020
DOI: 10.1002/jum.15563
|View full text |Cite
|
Sign up to set email alerts
|

Residual Lung Injury in Patients Recovering From COVID‐19 Critical Illness

Abstract: Scarce data exist regarding the natural history of lung lesions detected on ultrasound in those who survive severe COVID-19 pneumonia.Objective-We performed a prospective analysis of point-of-care ultrasound (POCUS) findings in critically ill COVID-19 patients during and after hospitalization.Methods-We enrolled 171 COVID-19 intensive care unit patients. POCUS of the lungs was performed with phased array (2-4 MHz), convex (2-6 MHz) and linear (10-15 MHz) transducers, scanning 12 lung areas. Chest computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 98 publications
1
23
0
1
Order By: Relevance
“…The lungs are the organ most likely to sustain serious injury from COVID-19 [29,30]. Even mildly symptomatic patients may have lung involvement on CT imaging [31] and persistent alterations of pulmonary function tests (PFTs) [8,18,29,[32][33][34][35][36][37][38].…”
Section: Respiratory Systemmentioning
confidence: 99%
“…The lungs are the organ most likely to sustain serious injury from COVID-19 [29,30]. Even mildly symptomatic patients may have lung involvement on CT imaging [31] and persistent alterations of pulmonary function tests (PFTs) [8,18,29,[32][33][34][35][36][37][38].…”
Section: Respiratory Systemmentioning
confidence: 99%
“…An Italian study revealed that 54 (29.2%) of survivors experienced shortness of breath (SOB) and tachypnoea 21 . Similarly, a Chinese study and a Saudi study revealed that 115 (21.4%) of the survivors had tachypnoea even after mild activity, and 48.8% had difficulty of breathing that impedes them from completing a 6-minute walk test 23,31 . These symptoms are common among obese patients, ICU survivors, senior survivors, and patients with previous respiratory diseases 16 .…”
Section: Respiratory Sequelaementioning
confidence: 93%
“…The duration of the follow-up ranged from 6 weeks to 4 months post hospital discharge 30, 38, 4231 (Table 1). Worsened breathlessness / dyspnoea is one of the common reported symptoms post COVID-19 infection 23,26,27,31,33,40,47 . According to the results reported in a British study, 29 (42.6%) and 21 (65.6%) patients who discharged from ICU and ward respectively suffered from moderate to severe breathlessness for several weeks post-discharge 16 , while a prospective study reported significant breathlessness among 64% of the survivors up to 3 months post-discharge 35 .…”
Section: Respiratory Sequelaementioning
confidence: 99%
See 1 more Smart Citation
“…Another study noted that point-of-care ultrasound findings, performed after hospital discharge, assist in monitoring the progress of severe COVID-19 pneumonia. During follow-up, besides LUS, chest CT was used for patients with suspected residual lung injury as well as CT pulmonary angiography and echocardiography for patients with residual thromboembolic disease[ 107 ].…”
Section: Challenges For the Radiology Departmentmentioning
confidence: 99%